CircZBTB44 promotes renal carcinoma progression by stabilizing HK3 mRNA structure - Tushuai Li; Yue Gu; Baocai Xu; Kamil Kuca; Jie Zhang; Wenda Wu (Molecular Cancer)
Abstract CircZBTB44 (hsa_circ_0002484) has been identified to be upregulated in renal cell carcinoma (RCC) tissues, while its role and contribution in RCC remain elusive. We confirmed the overexpression of circZBTB44 in RCC cells compared to normal kidney cell HK-2. CircZBTB44 knockdown suppressed the viability, proliferation, and migration of RCC cells and inhibited tumorigenesis in xenograft mouse models. Heterogeneous Nuclear Ribonucleoprotein C (HNRNPC) and Insulin-like growth factor 2 mRNA-binding protein 3 (IGF2BP3) are two RNA binding proteins of circZBTB44. HNRNPC facilitated the translocation of circZBTB44 from nuclei to cytoplasm via m6A modification, facilitating the interaction of IGF2BP3 and circZBTB44 in the cytoplasm of RCC cells. Furthermore, circZBTB44 upregulated Hexokinase 3 (HK3) expression by binding to IGF2BP3 in RCC cells. HK3 exerted oncogenic effects on RCC cell malignant behaviors and tumor growth. In the co-culture of RCC cells with macrophages, circZBTB44 promoted M2 polarization of macrophages by up-regulating HK3. In summary, HNRNPC mediated circZBTB44 interaction with IGF2BP3 to up-regulate HK3, promoting the proliferation and migration of RCC cells in vitro and tumorigenesis in vivo. The results of the study shed new light on the targeted therapy of RCC.